Neutral aldoses derived from sequential acid hydrolysis of sediments as indicators of diagenesis over 120, 000 years. (April 2015) - Quijada, Melesio; Riboulleau, Armelle; Guerardel, Yann; Monnet, Claude; Tribovillard, Nicolas
Highlights: Carbohydrates from recent Cariaco sediments were analyzed via sequential hydrolysis. Neutral aldoses represented 1.7–3.7% of the total organic carbon. Abundant labile storage sugars decreased downwards. Minor refractory sugars reflected the original primary signature. Abstract: Neutral aldoses of the upper 50 m (representing ca. 120 kyr) of sediments from the Cariaco Basin were studied using a new technique based on water extraction followed by sequential acid hydrolysis with 2N, 4N and 6N trifluoroacetic acid (TFA) to investigate the fate of carbohydrates during diagenesis. The distribution and abundance of neutral aldoses and their evolution with depth shed light on the origin and fate of carbohydrates upon burial. The carbohydrates originated mainly from phytoplanktonic production, in particular diatoms. The porewater carbohydrate fraction was invariant and its composition attested to considerable biodegradation of the source material. Bacteria in the sediment may have also contributed to this fraction. The carbohydrates in the 2N fraction represented a decreasing fraction of the total organic carbon (TOC) with increasing depth/age. This fraction likely derived from storage polysaccharides, which were progressively degraded in the sediment. The 4N fraction was dominated by hexoses, suggesting that it comprised sugars derived from structural polysaccharides and exopolymeric substances. It showed a slight decrease with depth, over the 120 kyr. The 6N fraction comprised a relatively constant fraction of TOC with sediment depth. The aldose distribution suggested that the 6N fraction showed the imprint of the initial biological signal preserved by a proteinaceous macromolecular structure and/or a mineral matrix, but not from condensation in the sediment of more labile polysaccharides.